Selectivity of Ethyl Acetate Fraction of Gynura Procumbens on Colon Cancer and Breast Cancer - Nurulita, Nunuk Aries; Meiyanto, Edy; Sugiyanto, . (Indonesian Journal of Cancer Chemoprevention, 2011)
Gynura  procumbens  is  widely  used  as  traditional  remedy  in  South-East  Asia.  Gynura procumbens exhibites anti inflammatory, antioxidant, and reduced blood pressure activity. The aim of this study was to determine chromatographic profile of ethyl acetate fraction of  Gynura procumbens (FEG) and to investigate its cytotoxic properties and selectivity to colon cancerand breast cancer cancer cells. The chromatographic profile of FEG was determined using HPTLC densitometric  and  HPLC.  MTT  (3-(4,5-dimethyl-thiazol-2-yl)-2,5-diphenyltetrazolium  bromide) assay was performed to determine the growth inhibitory effect of FEG on the growth of WiDr, MCF-7, and T47D cells. NIH3T3, a normal cells was used to determine the selectivity of FEG, which  contained  small  amount  of  quercetin  as  identified  from  chromatographic  profile  both HPTLC  and  HPLC.  FEG  inhibited  cell  growth  of  WiDr,  of  MCF-7  and  of  T47D  cells  in  time dependent manner. Quercetin affected cell growth inhibition approximately two fold higher at WiDr and MCF-7, whereas FEG had lower effect on T47D cell. Quercetin did not seem as the main  active  compound  of  FEG.  At  this  study,  FEG  caused  less  inhibition  on  the  growth  of NIH3T3 cells than that of on all cell lines. Selectivity index (SI) of FEG on WiDr, MCF-7 and T47D were 4.97, 2.77 and 7.79 respectively. According to the datas obtained, FEG possesses moderate to high cytotoxicity properties on WiDr, MCF-7 and T47D cells. FEG demonstrates selective  effect  against  cancer  cells  and  reveals  prospective  properties  as  cancer chemoprevention agent.Keywords: Gynura procumbens, colon cancer, breast cancer, cytotoxicity, selectivity